Przesłanki prawne zarządzania ryzykiem środowiskowym - Panasiewicz, Agnieszka (Legal premises of the environmental risk management, 2006)
The growing number of industrial catastrophes is the main reason for searching means to decrease the possibility of the occurrence of such events. The most important are: early discovery of the risk, foreseeing accident’s effects and preparing a special programme of risk management. A special role is assigned to the environmental risk management, therefore the law regulations started to appear in many countries, obliging enterprises and governmental agencies to carry out the risk analysis and to prepare plans to prevent catastrophes or minimize their effects. In the European Union countries’ regulations special attention is paid to the environmental risk estimation and management. In the experts’ opinion it is very important for the reduction of the occurrence of ecological disasters.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 140-149